2023
DOI: 10.1097/adm.0000000000001207
|View full text |Cite
|
Sign up to set email alerts
|

Safety and Efficacy of Rapid Methadone Titration for Opioid Use Disorder in an Inpatient Setting: A Retrospective Cohort Study

Sukhpreet Klaire,
Nadia Fairbairn,
Andrea Ryan
et al.

Abstract: Objectives Inpatient guidelines for methadone titration do not exist, whereas outpatient guidelines lack flexibility and do not consider individual opioid tolerance. The evaluation of rapid, adaptable titration protocols may allow more patient-centered and effective treatment for opioid use disorder in the fentanyl era. Methods This study performed a retrospective chart review of patients 18 years or older with opioid use disorder who were initiated on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…Few data exist about dosing for patients using fentanyl; however, clinical experience and emerging evidence suggests that patients may need higher doses of methadone and buprenorphine . The heterogenous and rapidly changing drug supply means any specific dosing guidance (including the guidance outlined in this review) will likely change over time and may need to be modified to adapt to the current local drug supply, patient use patterns, and emerging evidence.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Few data exist about dosing for patients using fentanyl; however, clinical experience and emerging evidence suggests that patients may need higher doses of methadone and buprenorphine . The heterogenous and rapidly changing drug supply means any specific dosing guidance (including the guidance outlined in this review) will likely change over time and may need to be modified to adapt to the current local drug supply, patient use patterns, and emerging evidence.…”
Section: Methodsmentioning
confidence: 99%
“…The traditional methadone initiation approach was developed decades ago in ambulatory settings and is often insufficient to manage severe withdrawal and craving from regular fentanyl use. Clinical experience and early evidence from hospital addiction consultation services has demonstrated that patients, especially those using fentanyl, can undergo more rapid dose titration while hospitalized . Clinicians should consider harms of untreated or undertreated OUD with potential harms of rapid methadone titration.…”
Section: Methodsmentioning
confidence: 99%